Analisis Kelayakan Jeruk Dekopon (Studi Kasus : Bagus Agro Pelaga, Kecamatan Petang, Kabupaten Badung) - PRADNYADHIKA S., PUTU BAGUS KRESNA; BUDIASA, I WAYAN; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Analysis of Dekopon Orange Feasibility (Case Study : Bagus Agro Pelaga, Petang District, Badung Regency) Dekopon is one of the oranges tribe which began to be developed in Indonesia and Bagus Agro Pelaga was the pioneer in the development of this kind of orange in Bali. The purpose of this study was to determine the financial feasibility of dekopon oranges in Bagus Agro Pelaga financially as seen from the investment criteria and the constraints in developing the business. The analysis used in this study is the investment criteria method including NPV, IRR, Net B / C, Payback Period and sensitivity analysis. The results of this study indicate that the dekopon farming in Bagus Agro Pelaga is financially feasible to be cultivated. Based on the feasibility study of dekopon farming in Bagus Agro Pelaga, NPV values ??of Rp2,341,918,186.00, IRR of 36%, Net B / C of 3.78, Payback Period for 3 years 2 months, and the results of sensitivity analysis with three different scenarios also show that dekopon oranges are still declared feasible to be developed. Suggestions that can be given include continuing dekopon farming with more innovations and further research to overcome the obstacles faced by Bagus Agro Pelaga's management, such as creating a special department that focuses on selling Bagus Agro Pelaga agricultural products.